Capital Punishment without Capital Trials in Japan’s Lay Judge System - David T. Johnson (Asia-Pacific Journal)
In May 2009, Japan began a new trial system in which ordinary citizens sit with professional judges in order to adjudicate guilt and determine sentence in serious criminal cases. This change injected a meaningful dose of lay participation into Japanese criminal trials for the first time since 1943, when Japan's original Jury Law was suspended during the Pacific War. In May 2010, newspapers reported that the new system "has had a smooth first year," though they also stressed that it "has yet to be really tested by cases involving complex chains of evidence or demands by prosecutors for the death sentence."The new system is being tested in its second year. In June-Jul 2010, lay judge panels handed down three complete or partial acquittals in cases involving complex evidence and defendants who denied guilt, causing some prosecutors to contend that the new system makes it "harder and harder to persuade lay judges that defendants are guilty"-despite the fact that these not-guilty verdicts were the first that lay judges had rendered in more than 600 trials. In September, a lay judge panel in Tokyo evaluated the contradictory claims of medical experts and endured two weeks of frenzied media coverage before convicting actor Oshio Manabu and sentencing him to two-and-one-half years in prison for failing to call an ambulance to aid Tanaka Kaori, who died of an overdose of Ecstasy (MDMA) that Oshio had given her when they met to have sex in a Roppongi apartment (prosecutors wanted a six-year sentence). And in October, Japanese citizens started to decide who the state should kill. By the end of 2010, lay judge panels had made five capital decisions, resulting in one life sentence, three death sentences, and one acquittal.This article examines a series of recent death penalty judgments under Japan's new lay judge system.